Anatomic and functional outcomes of retinectomy for the management of complicated retinal detachment with proliferative vitreoretinopathy - Tranos P; Vakalis A; Asteriadis S; Lokovitis E; Georgalas I; Stravrakas P (Dove Medical Press, 2015)
Paraschos Tranos,1 Athanasios Vakalis,1 Solon Asteriadis,1 Evaggelos Lokovitis,1 Ilias Georgalas,2 Panagiotis Stavrakas3 1Ophthalmica Eye Institute, Thessaloniki, Greece; 2First Department of Ophthalmology, 3Second Department of Ophthalmology, University of Athens Medical School, Athens, Greece Abstract: The aim of this study is to report the anatomic and functional outcomes of retinectomy for the management of rhegmatogenous retinal detachment complicated by proliferative vitreoretinopathy (PVR), comparing them with previously reported data and determining prognostic factors. Fifty-one eyes of 51 patients with established PVR grade C in which retinectomy was performed were retrospectively enrolled in the study. Primary outcome measures were anatomic success rate and final visual acuity. Secondary outcome measures were intraoperative complications, number of re-operations, and postoperative hypotony. Prognostic factors in relation to retinal re-attachment and final visual acuity were retrospectively analyzed. The rate of complete retinal re-attachment after one operation was 80% and after two operations it was 84%. At the end of the follow-up, the macula was attached in 96% of the cases. Mean LogMAR best-corrected visual acuity (BCVA) improved significantly from 2.45±0.66 preoperatively to 1.37±0.75 at the end of the follow-up (P<0.001). BCVA improved in 37 eyes (72%), remained the same in eleven eyes (22%) and worsened in three eyes (6%). Postoperative hypotony was observed in 2% of cases. Postoperative BCVA was significantly correlated with preoperative BCVA (P<0.001), extension of PVR (P=0.013), preoperative use of gas instead of silicone oil (SO) (P=0.01), and removal of SO (P=0.05). SO was left in situ in 35% of eyes. In conclusion, retinectomy is a surgical option providing good anatomical and reasonable visual outcomes in complicated retinal detachment with PVR. Better preoperative visual acuity, lesser extension of PVR, and the use of gas tamponade during the primary repair are relevant factors for a successful outcome whereas re-proliferation of epiretinal membranes seems to be the main reason of anatomical failure. Keywords: retinal detachment, proliferative vitreoretinopathy, vitrectomy, retinectomy